2018
DOI: 10.1080/16549716.2019.1603515
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing gender inequalities in self-assessed health status in Liberia

Abstract: Background: Understanding the magnitude of inequalities and drivers for reducing genderrelated health inequalities is crucial in developing countries. This is particularly the case for Liberia with its very high level of gender-related inequalities in health and health outcomes. Objective: This paper assesses the magnitude of gender health inequalities and the relative contribution of different factors to health inequality in Liberia. Methods: Data came from the Liberian Household Income Expenditure Survey 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
8
0
3
Order By: Relevance
“…Countries with high U5D and high pro-female inequality (like Liberia and Lesotho in this study) usually have the problem of female inequality as the U5D pattern does not fit into the natural pattern. High gender inequalities have been reported from both Liberia [ 37 ] and Lesotho [ 38 ] with the latter country also struggling with the effect of HIV which have been shown to have a higher impact on women [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Countries with high U5D and high pro-female inequality (like Liberia and Lesotho in this study) usually have the problem of female inequality as the U5D pattern does not fit into the natural pattern. High gender inequalities have been reported from both Liberia [ 37 ] and Lesotho [ 38 ] with the latter country also struggling with the effect of HIV which have been shown to have a higher impact on women [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the interpretation of Oaxaca decomposition should be carefully assessed. Some studies only present the differences due to characteristics and do not attempt to assess the unexplained components or constant terms [ 24 , 25 ]. With further development of Oaxaca decomposition moving towards including time-varying covariates, this could be an interesting tool to investigate group differences over time [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…55 A similar study in Uganda found that poor households would benefit from tailored programmes and additional assistance to support greater access to mobile money services. 56 In some countries, various laws and regulations have limited ICTs for cross-border financial flows. While it is important to ensure digital security and prevent illicit financial transfers, overly cumbersome and rigid regulations have often driven up the cost of sending remittances, for example, and slowed the uptake of new technologies needed to enhance financial inclusion.…”
Section: The Economic Contributions Of Migrantsmentioning
confidence: 99%